2010
DOI: 10.1007/s10344-010-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of European hedgehogs (Erinaceus europaeus) in Britain: epidemiological study and coprological test evaluation

Abstract: Seventy-four European hedgehogs (Erinaceus europaeus) that had died in wildlife rehabilitation centres were dissected and their parasite burdens documented. Overall parasite prevalence was 91%, and a total of six helminth species were isolated: five nematodes (Crenosoma striatum, Eucoleus aerophilus, Capillaria erinacei, Capillaria ovoreticulata and Capillaria spp.), one trematode (Brachylaemus erinacei) and one acanthocephalan (Oliganthorhynchus erinacei). The tick Ixodes hexagonus and flea Archeopsylla erina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 22 publications
5
56
2
Order By: Relevance
“…Such few eggs passing from these helminths were undetectable by the flotation method. These results are in contrast with the findings of Gaglio et al (18), who found numerous types of helminthic eggs in European hedgehogs in Britain using the MC Master Method. The reason for the contrast in results could be related to the different climatic conditions in Iran and Britain and consequently different parasitic burden in wildlife animals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Such few eggs passing from these helminths were undetectable by the flotation method. These results are in contrast with the findings of Gaglio et al (18), who found numerous types of helminthic eggs in European hedgehogs in Britain using the MC Master Method. The reason for the contrast in results could be related to the different climatic conditions in Iran and Britain and consequently different parasitic burden in wildlife animals.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, the present study was conducted to identify the endoparasites of long-eared hedgehogs from the Zabol district in Southeast Iran to help understand wildlife parasitic disease and decrease the risk of zoonotic pathogen transmission in the area. One of the simplest and advantageous monitoring methods to find live hedgehog helminths is the use of flotation methods (18). The stool flotation method was used in Iranian hedgehogs in the present study for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…On seeing from dorsal side mouthpart observed in anterior parts, palps and hypostome were short, basis capituli distinctly appeared hexagonal shape and length of palp was nearly equal to basis capituli. Several studies have been conducted worldwide which showed high prevalence of this ectoparasite on hedgehog [10,9,19] . This tick had high tendency to infect wild host and immature stages generally infest hedgehogs, gerbils and rodents [3] .…”
Section: Resultsmentioning
confidence: 99%
“…The hedgehog is also of interest to many members of the public because it is reported to be declining in the UK and is a priority species nationally and in many local areas under the Biodiversity Action Plan framework (Hof and Bright 2009;Gaglio et al 2010). Its decline is thought to be caused by a combination of factors including the loss of suitable habitat such as hedgerows and uncultivated field margins, a high level of mortality on roads, predation and competition by badgers, and high concentrations of pesticides that diminish invertebrate food supplies (Ward et al 1997;Wilson et al 1999;Huijser and Bergers 2000;Young et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the hedgehog's current decline (Hof and Bright 2009;Gaglio et al 2010), it is especially important that data collected by volunteers are as accurate as possible, and this should include reliable absence data.…”
Section: Introductionmentioning
confidence: 99%